Analysis of the Application of Occupational Safety and Health in Structural Work in the South Sulawesi Education Quality Assurance Institute (LPMP) Building Renovation Project - Marlina Pasarong; Junus Mara; Helen Adry Irene Sopacua (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The appIication off occupationaI heaIth and sahfety (K3) is never dry in the context of the scientific ocean. Either in an academic research or in a practical study. K3 issues are constantly raised in the discussion of academic papers, be it journals or final assignments. Of course, the